The Relationship Between A History of Chronic Energy Deficiency During Pregnancy and Mother’s Nutritional Knowledge Levels with Underweight Infants - Misdawati; Nurhamidi; Aprianti; Pratiwi, Niken (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
The prevalence of underweight toddlers aged 0-59 months at the Tabunganen Community Health Center reached 18.58% (exceeding the national target of 12%). This was due to chronic energy deficiency during pregnancy (52.3%) and poor nutritional knowledge resulting from economic constraints and limited access to food in coastal areas, threatening the quality of human resources through fetal growth disorders and poor eating habits. The objective of this study is to analyze the relationship between a history of chronic energy deficiency during pregnancy and the level of maternal nutritional knowledge with the occurrence of underweight in infants. This study is an analytical cross-sectional study (n=92 mothers and children, October-November 2025) measuring history of CEM (LILA<23.5 cm from KIA), nutritional knowledge (questionnaire), and underweight (BBU Z-score -3 sd -2 SD, WHO) using the Chi-square test in JASP (α=0.05). Results showed that the prevalence of KEK was 19.6%, good knowledge was 59.8%, and underweight was 33.7%. There was no significant relationship between KEK (p=0.554) or nutritional knowledge (p=0.562) and underweight in toddlers, indicating the dominance of economic factors, feeding practices, and infections. Implications: Strengthen integrated nutrition interventions through posyandu (applied education, PMT, BBU monitoring), cross-sector collaboration for food access, to sustainably reduce the prevalence of underweight in vulnerable areas.